The Use of Hello English Application in Improving Students’ Vocabulary Mastery - Nur Irmayanti; Khadijah Maming; Ilham Sahabuddin; Hasman Hasman (Edumaspul: Jurnal Pendidikan, 2024)
Hello English is an English learning application used to help users improve their English language skills. The application presents a variety of learning materials, interactive exercises, and games designed to improve students' vocabulary. Therefore, this study aims to see whether students' vocabulary mastery can improve by using the Hello English application. The researchers applied the pre-experimental method with one group pre-test and post-test design in this study. The population of this study were eighth grade students of SMPN 10 Parepare. The sample of this study was eighth grade students consisting of 27 students, students were selected using simple random sampling. The form of pre-test given was 10 forms of matching test and 10 forms of fill the blank. The results showed that the pre-test scores of eighth grade students improved after being taught using Hello English application. The average score obtained by students through the pre-test was 68.51 and the post-test was 77.96. This is supported by the hypothesis test obtained t table value of 1.705. Thus, because the calculated t-test of 8.256 > 1.705, the basic selection of decision making is H0 rejected and Ha accepted. which means the Hello English application can improve the vocabulary mastery of eighth grade students of SMPN 10 Parepare. In addition, students also look active and enthusiastic in the learning process by using the Hello English application as a learning media.